Surface Properties of Silicas with Chemically Bonded Polyfluoroalkyl Groups - K.B. Gurevich; T.M. Roshchina; N.K. Shonia; L.M. Kustov; A.V. Ivanov (Adsorption Science & Technology)
Adsorption isotherms of hexane and benzene were measured on silicas with chemically bonded polyfluoroalkyl groups and the thermodynamic characteristics of the adsorption of n-alkanes, benzene and alkylbenzenes on the same materials studied at zero coverage by gas chromatography (GC). The prepared polyfluoroalkylsilicas were also investigated by IR spectroscopy over the spectral range 6000–2000 cm −1 when it was shown that the residual SiOH groups on the silica surface do not take part in the adsorption process as the attached organic groups effectively screen them. The polyfluoroalkylsilicas exhibited an extremely low adsorption potential and high polarity relative to unmodified alkylsilicas. The specific surface areas of the chemically modified silicas could be evaluated by comparison of their GC entropy values with those calculated from an ideal two-dimensional gas model.